C-Type Lectin Receptors in Antiviral Immunity and Viral Escape - Bermejo-Jambrina, Marta; Eder, Julia; Helgers, Leanne C.; Hertoghs, Nina; Nijmeijer, Bernadien M.; Stunnenberg, Melissa; Geijtenbeek, Teunis B. H. (Frontiers in Immunology, 2018)
C-type lectin receptors (CLRs) are important pattern recognition receptors involved in recognition and induction of adaptive immunity to pathogens. Certain CLRs play an important role in viral infections as they efficiently interact with viruses. However, it has become clear that deadly viruses subvert the function of CLRs to escape antiviral immunity and promote infection. In particular, viruses target CLRs to suppress or modulate type I Interferons that play a central role in the innate and adaptive defense against viruses. In this review we discuss the function of CLRs in binding to enveloped viruses like HIV-1 and Dengue virus, and how uptake and signaling cascades have decisive effects on the outcome of infection.